2016
DOI: 10.1016/j.jpsychires.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Is third trimester serotonin reuptake inhibitor use associated with postpartum hemorrhage?

Abstract: As serotonin reuptake inhibitor (SRI) use may decrease platelet function, previous research has shown a relationship between SRI use and an increased risk for bruising and bleeding. The literature regarding the association between SRI use during pregnancy and increased bleeding at delivery, referred to as postpartum hemorrhage (PPH), is mixed. In secondary analyses from two prospective observational studies of pregnant women with mood disorders, 263 women were exposed to an SRI (n=51) or not (n=212) in the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The two studies that have not reported this association have had 18 or fewer exposed cases. 22,23 Our results are in line with previous large studies, each with more than 55 exposed cases, that found antidepressant use late in pregnancy was associated with an increased risk of PPH. 13,14,[16][17][18][19] Related to our finding that higher sustained doses of antidepressants were associated with higher PPH risk, one previous study among low-income women reported a dose response for serotonin reuptake inhibitors (SRI), but not non-SRIs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The two studies that have not reported this association have had 18 or fewer exposed cases. 22,23 Our results are in line with previous large studies, each with more than 55 exposed cases, that found antidepressant use late in pregnancy was associated with an increased risk of PPH. 13,14,[16][17][18][19] Related to our finding that higher sustained doses of antidepressants were associated with higher PPH risk, one previous study among low-income women reported a dose response for serotonin reuptake inhibitors (SRI), but not non-SRIs.…”
Section: Discussionsupporting
confidence: 91%
“…[8][9][10][11][12][13][14][15][16][17][18][19] Other studies,generally those with smaller numbers of exposed cases, conclude no association between antidepressants and preeclampsia and PPH. [20][21][22][23] Recently, studies have used longitudinal cluster analysis to classify medication use during pregnancy instead of a dichotomous "any use" versus "no use" approach. [24][25][26][27][28] These methods classify individuals with similar patterns of use, allowing for comparisons across groups with less within-group heterogeneity in dose and gestational timing of use that may be important for understanding risks for preeclampsia and PPH.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluated association of SSRIs with risk of postpartum hemorrhage and found no association between them (Kim et al 2016). Currently, it is recommended that women should be encouraged to breast feed while being treated with antidepressants (Kim et al 2014).…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri):-mentioning
confidence: 99%
“…16 Some studies have reported a higher risk of postpartum haemorrhage (PPH) among women on SSRIs, especially if used during the third trimester of pregnancy or in imminent proximity to the delivery. 5,10,[17][18][19] Others, however, have failed to confirm such an association, 8,12,20,21 possibly due to the small size of the exposed population and hence low statistical power, 8,21 as well as differences in the definition of the studied outcome. 8,12,20,21 The most accepted biologically plausible mechanism by which use of SSRI influences the risk of bleeding is by haemostasis impairment, through a decrease in platelet aggregation and function.…”
Section: Introductionmentioning
confidence: 99%